Pengaruh Muqri’ Sumatera Utara dalam Ajang Internasional - Muhammad Jihad Azni Lubis; Asniati Asniati; Maharani Maharani; Ahmad Sobri; Salahuddin Harahap (STIKes Ibnu Sina Ajibarang, 2024)
Sheikh Azra'i Abdurrauf is a muqri from North Sumatra who masters the sciences of the Koran such as tajwid, fashahah, tafsir, and the science of qira'at. However, as a cleric who played a role in producing Al-Quran scholars and scientists for the next generation, his character and role are not visible in historical records and tend to disappear with his death, if no one uncovers and re-examines the role of this cleric. in written form, it is feared that the history and role of the Islamic scholar Sheikh Azra'i Abdurrauf will be lost. The aim of this research is to review the role of influential Al-Quran scholars from North Sumatra who are active and active in the international arena so that they remain visible in historical records and are not forgotten and provide motivation. for students of the Koran, qori-qoriah, and successors of the Koran in the future. In this research, the author used the library research method, namely searching for and collecting books related to the research discussion, the results of this research are understandable a muqri from North Sumatra, Syakh Azra'I Abdurrauf is very influential in the national and international arena because of his work and achievements as a judge on the Musabaqah Tilawatil Quran (MTQ) national and international level, teaching at the Jakarta Al-Quran Science College (PTIQ), filling in IZA 'AH in Saudi Arabia and received an award as a professor of hafizd of the Koran.